Maternal sucrose-rich diet and fetal programming: changes in hepatic lipogenic and oxidative enzymes and glucose homeostasis in adult offspring - D'alessandro, Maria Eugenia Guadalupe (2013)
Nutritional insults during pregnancy and lactation (P+L) are often associated with offspring health risks. We investigated the effect of maternal exposure to a sucrose-rich diet (SRD) during P+L on glucose and lipid metabolism of adult offspring regardless of post-weaning diet. Dams were fed an SRD or a control diet (CD) during P+L. After weaning, male offspring from SRD and CD dams were divided in two groups and fed a CD or SRD until 150-days old forming CD-CD, CD-SRD, SRD-SRD and SRD-CD groups. Offspring where SRD was fed at any period of life showed: 1) Increased adipose tissue weight without changes in final body weight; 2) Dyslipidemia as result of increased very low density lipoprotein triglyceride secretion rate and decreased triglyceride clearance; 3) Hepatic steatosis associated with increased activity of key enzymes involved in liver de novo lipogenesis and significant decrease of the activity of mitochondrial fatty acid oxidation enzyme. These results were more pronounced in CDSRD and SRD-SRD groups. 4) Hyperglycemia without changes in insulin levels, plus a deterioration of intravenous glucose tolerance and intraperitoneal insulin tolerance test. We hypothesized that SRD during P+L could be associated with a programming effect on glucose homeostasis and hepatic lipid metabolism that predispose offspring to develop later-life insulin resistance and metabolic disorders, regardless of post-natal diet. Journal of citation of citation Reports Thomson reuters: IF: 2.694. Paper aceptado (10-12-13) y en prensa.